Etiology, pathological characteristics, and clinical management of black pleural effusion: A systematic review. Issue 8 (25th February 2022) - Yousaf, Zohaib; Ata, Fateen; Chaudhary, Haseeb; Krause, Florian; Illigens, Ben Min-Woo; Siepmann, Timo
Abstract: Background: Pleural effusion is characterized by excessive fluid collection in the pleural cavity. Black pleural effusion (BPE) is a rare entity with only limited scientific data. We aimed to review the current literature on black pleural effusion to characterize demographics, etiology, clinical presentation, pathological findings, available treatment strategies, and prognosis of this rare condition. Methods: We performed a systematic review of case reports and series and synthesized data on demographics, manifestations, management, and outcomes of patients with BPE. We searched Cochrane Library, PubMed, SCOPUS, and Google Scholar for any date until January 10, 2021. All studies (n = 31) that reported black pleural effusion in patients were added to the review. Prospective Register of Systematic Reviews registration number: CRD42020213839. Summary and descriptive analysis was performed on Jamovi version 1.2. Results: The mean age of 32 patients with BPE was 53 years, with male predominance (69%). The commonest risk factor was smoking (n = 9) followed by alcohol intake (n = 8). Dyspnea was the commonest symptom (n = 24, 75%). Pleural fluid was mostly exudative (n = 21). The commonest associated diagnosis was malignancy (n = 14), with 50% secondary to metastatic melanoma. The commonest intervention was therapeutic thoracocentesis (n = 25, 78%), and the effusion recurred in half of the cases where recurrence was reported (n = 13). In our review, we found the mortality rate to be at 20.8% (n = 20.8%). 58.3% of the patients were successfully treated and discharged home (n = 14). Conclusion: Although rare, BPE appears to be a relevant symptom as it seems to be frequently associated with modifiable risk factors and underlying malignancy. Our systematic review substantiates a vital research gap as observational research is imperative to characterize BPE further and form a basis for designing tailored diagnostic, preventive, and therapeutic strategies for BPE.